Impact of Changes in Systemic Physiology on fNIRS/NIRS Signals: Analysis Based on Oblique Subspace Projections Decomposition (2018)
Measurements of cerebral and muscle oxygenation (StO2) and perfusion ([tHb]) with functional near-infrared spectroscopy (fNIRS) and near infrared spectroscopy (NIRS), respectively, can be influenced by changes in systemic physiology. The aim of our study was to apply the oblique subspace projections signal decomposition (OSPSD) to find the contribution from systemic physiology, i.e. heart rate (HR), electrocardiography (ECG)-derived respiration (EDR) and partial pressure of carbon dioxide (pCO2) to StO2 and [tHb] signals measured on the prefrontal cortex (PFC) and calf muscle. OSPSD was applied to two datasets (n1 = 42, n2 = 79 measurements) from two fNIRS/NIRS speech studies. We found that (i) all StO2 and [tHb] signals contained components related to changes in systemic physiology, (ii) the contribution from systemic physiology varied strongly between subjects, and (iii) changes in systemic physiology generally influenced fNIRS signals on the left and right PFC to a similar degree.